The Relationship Of Family Duty Implementation With DM Patient's Compliance In Prolanis Activities In The Work Area Of Bojonegoro Public Health Center - Wiwik Utami; Dwi Agung Susanti; Nur Azizah; Wiwik Muhidayati; Anggi Reza (HealthCare Nursing Journal, 2023)
The Chronic Disease Management Program (Prolanis) is a health service with a proactive approach that is carried out in an integrated manner for people with diabetes mellitus and hypertension. The aim of the study was to determine the relationship between the implementation of family tasks and the compliance of Diabetes Mellitus patients in Prolanis activities. Design of analytic research with cross sectional approach. The population of prolanis DM participants was 84 people with simple random sampling with a sample of 69 respondents. Variable Independent implementation of family tasks and dependent DM patient compliance. Data processing begins with editing, coding, scoring, tabulating, and is analyzed using the Chi Square test and Coefficient Contingency, which are presented in tabular and narrative form. The results of the study were all 11 respondents (100.0%) who carried out family duties well, were obedient to Prolanis activities. Chi Square test results obtained P value = 0.010 < (0.05), so H0 was rejected, then H1 was accepted with a Coefficient Contingency value of 0.342. The conclusion is that there is a relationship between the implementation of family tasks and adherence of DM patients in Prolanis activities. Families must increase support, remind the schedule of Prolanis activities, pick up and drop off and increase access to participate in Prolanis activities.